EPCT-03. SERIAL PLASMA AND CSF CELL-FREE TUMOR DNA (CF-TDNA) TRACKING IN DIFFUSE MIDLINE GLIOMA PATIENTS UNDERGOING TREATMENT WITH ONC201. (1st June 2021) - Cantor, Evan; Wierzbicki, Kyle; Tarapore, Rohinton S; Thomas, Chase; Cartaxo, Rodrigo; Yadav, Viveka Nand; Ravindran, Ramya; Bruzek, Amy K; Wadden, Jack; Babilla, Clarissa May; Kawakibi, Abed Rhaman; Ji, Sunjong; et al.
Abstract: Diffuse midline glioma (DMG) with the H3K27M mutation is a lethal childhood brain cancer, with patients rarely surviving 2 years from diagnosis. We conducted a multi-site Phase 1 trial of the imipridone ONC201 for children with H3K27M-mutant glioma (NCT03416530). Patients enrolled on Arm D of the trial (n=24) underwent serial lumbar puncture (baseline, 2, 6 months) for cell-free tumor DNA (cf-tDNA) analysis at time of MRI. Additionally, patients on all arms of the trial at the University of Michigan underwent serial plasma collection. CSF collection was feasible in this cohort, with no procedural complications. We collected 96 plasma samples and 53 CSF samples from 29 patients, including those with H3F3A (H3.3) (n=13), HIST13HB (H3.1) (n= 4), and unknown H3 status/not biopsied (n=12) [range of 0–8 CSF samples and 0–10 plasma samples]. We performed digital droplet polymerase chain reaction (ddPCR) analysis and/or amplicon-based electronic sequencing (Oxford Nanopore) of cf-tDNA samples and compared variant allele fraction (VAF) to radiographic change (maximal 2D tumor area on MRI). Preliminary analysis of samples demonstrates a correlation between changes in tumor size and H3K27M cf-tDNA VAF, when removing samples with concurrent bevacizumab. In multiple cases, early reduction in CSF cf-tDNA predicts long-term clinical response (>1 year) to ONC201, and does not increase in cases of later-defined pseudo-progression (radiation necrosis). For example, a now 9-year old patient with thalamic H3K27M-mutant DMG underwent treatment with ONC201 after initial radiation and developed increase in tumor size at 4 months post-radiation (124% baseline) of unclear etiology at the time. Meanwhile, her ddPCR declined from baseline 6.76% VAF to <1%, which has persisted, with now near complete response (15% tumor reduction) at 30 months on treatment from diagnosis. In summary, we present the feasibility and utility of serial CSF/plasma monitoring of a promising experimental therapy for DMG.